2010
DOI: 10.3324/haematol.2009.019182
|View full text |Cite
|
Sign up to set email alerts
|

Value of allogeneic versus autologous stem cell transplantation and chemotherapy in patients with myelodysplastic syndromes and secondary acute myeloid leukemia. Final results of a prospective randomized European Intergroup Trial

Abstract: The online version of this article has a Supplementary Appendix. BackgroundAllogeneic stem cell transplantation is usually considered the only curative treatment option for patients with advanced or transformed myelodysplastic syndromes in complete remission, but post-remission chemotherapy and autologous stem cell transplantation are potential alternatives, especially in patients over 45 years old. Design and MethodsWe evaluated, after intensive anti-leukemic remission-induction chemotherapy, the impact of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 31 publications
4
45
0
Order By: Relevance
“…Recent results of a larger prospective randomized transplantation study showed no prognostic influence of IPSS or blast count on survival while advanced age, number of cytopenias and intermediate to high-risk cytogenetic characteristics were adverse prognostic factors. 40 A low and encouraging 2-year relapse incidence of only 16% was observed in this study, comparing favorably with incidences in previously published series. 5,33,40 Thus far, relapses have occurred only within the first 220 days after transplantation and no relapses have been reported beyond this time.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Recent results of a larger prospective randomized transplantation study showed no prognostic influence of IPSS or blast count on survival while advanced age, number of cytopenias and intermediate to high-risk cytogenetic characteristics were adverse prognostic factors. 40 A low and encouraging 2-year relapse incidence of only 16% was observed in this study, comparing favorably with incidences in previously published series. 5,33,40 Thus far, relapses have occurred only within the first 220 days after transplantation and no relapses have been reported beyond this time.…”
Section: Discussionsupporting
confidence: 75%
“…40 A low and encouraging 2-year relapse incidence of only 16% was observed in this study, comparing favorably with incidences in previously published series. 5,33,40 Thus far, relapses have occurred only within the first 220 days after transplantation and no relapses have been reported beyond this time. Rare late disease recurrences were noted by Nemecek et al who used the treosulfan-based conditioning regimen in a prospective allogeneic HSCT protocol, which included several disease entities.…”
Section: Discussionsupporting
confidence: 75%
“…100,101 In the absence of prospective data, but given the acceptable toxicity and potential for cytoreduction, we recommend pre-HCT azacitidine or decitabine therapy for patients in whom transplantation is being contemplated. Consistent with recommendations from the European LeukemiaNet and results from the European Intergroup Criant study, in which younger patients (,55 years) achieving CR to induction chemotherapy followed by HCT had a 4-year overall survival rate of 55%, compared with 41% for those not then receiving HCT (HR .81, 95% confidence interval .49-1.35), 102,103 a reasonable pretransplant strategy includes induction chemotherapy for younger MDS patients with very high blast percentages (.15%), favorable or intermediate-risk karyotype disease, and good performance status, or for those who progress on hypomethylating agent therapy. Patients with good-risk cytogenetics may enjoy durable remissions even without HCT.…”
Section: What Is the Most Appropriate Timing Of Hct?supporting
confidence: 62%
“…21,22 As a consequence, the implementation of comorbidity assessment into clinical practice requires the combined use of different scores. MDS-CI and HCT-CI are based on the same classification of comorbidities and may be used in a complementary manner to estimate the impact of comorbidity on the natural course of the disease and on the outcome after allogeneic transplantation, [31][32][33] respectively, thus providing the information for a proper evidence-based evaluation of the risk-benefit related to the transplantation choice.…”
Section: Discussionmentioning
confidence: 99%